CORRELATION AMONG SEMANTIC, SYNTACTIC, PRAGMATIC, AND COGNITIVE BARRIERS TOWARDS ACCURACY GEOMETRY PROOFS - Erna Iftanti; Umy Zahroh; Musrikah Musrikah (University of Kuningan, 2021)
The purpose of this article is to discover the correlation among language elements- semantic, syntactic, pragmatic- and cognitive barriers towards the accuracy of Geometry proofs. This interdisciplinary study was carried out in response to the fact that students of Math neither focus on mathematical procedures nor integrate the topics of math into the representation of mathematical concept which brings about the constraint of achieving the goal of learning Math. This fact is resulted from either external or internal factors such as students’ background knowledge that is influenced by cognitive or communicative factors. Thus, effective communication consisting of semantic, syntactic, and pragmatic can be big barriers towards achieving learning goal. This study was conducted through a correlational study with 30 students of Math Department, IAIN Tulungagung Indonesia as the sample out of 120 populations. They were selected randomly based on their own availability and willingness to seriously take part in this interdisciplinary research. The instrument used was a set of achievement Math test on triangle congruency. The findings of this study prove that there is a correlation and negative effect of semantic, syntactic, pragmatic, and cognitive barriers towards the accuracy of Geometry proof. The result of this study is pedagogically implemented for tutors of Math to consider either oral or written communicative barriers which inhibit the students’ learning success in Math. Further studies on efforts of minimizing language barriers in Geometry proof accuracy is suggested to be conducted.